Zealandia's oldest volutes (Mollusca: Gastropoda: Volutidae) from the early Paleogene of South Island and Chatham Islands: post Gondwana break-up and evolutionary divergence. (15th June 2016) - Stilwell, Jeffrey D.
Abstract: The isolation of Zealandia in the latest Cretaceous and early Paleogene following the final break-up of Gondwana fostered significant provincialism in molluscan faunas, concomitant with the segmentation of oceanic circulation patterns and changing climate nearing the end of the greenhouse phase in the Southwest Pacific. The earliest volutes (Gastropoda: Volutidae) from the Zealandian region reflect this isolation after separation from the Marie Byrd Land region of West Antarctica with several endemic groups being recognized for the first time since collecting first started in the Wangaloa Formation at Mitchells Rocks (Wangaloa), South Island, New Zealand in 1869. Five taxa attributed to the Volutidae are described herein from South Island (Wangaloa Formation and Steel Greensand) and also the Chatham Islands (Red Bluff Tuff) from the early (mid-Danian) to late Paleocene (Thanetian?). These comprise a new mid-Danian fulgorariine? genus and species, Wangaluta henaconstricta n. gen. n. sp.; a new combination also from the Wangaloa Formation, Wangaluta? neozelanica (Finlay and Marwick, 1937 ); two new zidonine volutes, the mid-Danian Alcithoe . s.l. wangaloaensis n. sp. from the Wangaloa Formation, and also Teremelon onoua n. sp. from the late Paleocene-early Eocene of the Red Bluff Tuff; and a probable volute, Fulgorariine? gen. indet. sp. indet. from the mid-Danian of the Steel Greensand. All of these taxa are endemic in the early Paleogene of New Zealand and represent a significant boost in our knowledge of post-K-Pg boundary diversification of volutid gastropods in the shrinking Weddellian Biotic Province in the southern rim of the Pacific.